Blockchain Governance and Regulation as an Enabler for Market Creation in Emerging Markets - Niforos, Marina (International Finance Corporation, Washington, DC, 2018)
Developing a proper governance and regulatory framework for blockchain-based applications will be essential to providing market participants the stability they need to fully engage with the technology and allowing innovation to flourish. Given the global, multi-sectoral reach of blockchain, regulators, and industry will have to work in a collaborative manner to ensure they can both experiment and learn, and so shape the future of the technology in a way that benefits all parties and society as a whole.